Apparent Prevalence of Beef Carcasses Contaminated with Mycobacterium avium subsp. paratuberculosis Sampled from Danish Slaughter Cattle - Hisako Okura; Nils Toft; Nicola Pozzato; Annalucia Tondo; Søren Saxmose Nielsen (Veterinary Medicine International)
Presence of Mycobacterium avium subsp. paratuberculosis (MAP) in beef has been reported as a public health concern because asymptomatically infected cattle may contain MAP in tissues that are used for human consumption. Associations between MAP carcasses contamination and animal characteristics such as age, breed, production type, and carcass classification were assessed. Cheek muscles from 501 carcasses were sampled cross-sectionally at a Danish abattoir and tested for presence of viable MAP and MAP DNA by bacterial culture and IS900 realtime PCR, respectively. Cheek muscle tissues from carcasses of two dairy cows were positive by culture whereas 4% of the animals were estimated with ≥10 CFU/gram muscle based on realtime PCR. Age was found to be associated with carcass contamination with MAP. The observed viable MAP prevalence in beef carcasses was low. However, detection of MAP and MAP DNA in muscle tissues suggested that bacteremia occurred in slaughtered cattle.